The Grimkes : the legacy of slavery in an American family - Greenidge, Kerri K. (Liveright Publishing Corporation, a division of W.W. Norton & Company, 2023)
"Sarah and Angelina Grimke--the Grimke sisters--are revered figures in American history, famous for rejecting their privileged lives on a plantation in South Carolina to become firebrand activists in the North. Their antislavery pamphlets, among the most influential of the antebellum era, are still read today. Yet retellings of their epic story have long obscured their Black relatives. In The Grimkes, award-winning historian Kerri Greenidge presents a parallel narrative, indeed a long-overdue corrective, shifting the focus from the white abolitionist sisters to the Black Grimkes and deepening our understanding of the long struggle for racial and gender equality"--